Association analysis of dietary habits with gut microbiota of a native Chinese community - Qian, Leimin (Exp Ther Med, 2018)
Environmental exposure, including a high-fat diet (HFD), contributes to the high prevalence of colorectal cancer by changing the composition of the intestinal microbiota. However, data examining the interaction between dietary habits and intestinal microbiota of the Chinese population is sparse. We assessed dietary habits using a food frequency questionnaire (FFQ) in native Chinese community volunteers. Based on the dietary fat content determined using the FFQ, the volunteers were divided into HFD group (≥40% of dietary calories came from fat) or low-fat diet (LFD) group (<40%). Fecal and colonic mucosal microbiota composition was determined using 16S rDNA based methods. In stool matter of HFD group, Prevotella and Abiotrophia showed significantly higher abundance, whereas unclassified genus of S24-7 (family level) of Bacteroidetes, Gemmiger, Akkermansia and Rothia were less abundant. On colonic mucosal tissue testing, unclassified genus of S24-7 showed significantly higher abundance while Bacteroides, Coprobacter, Abiotrophia, and Asteroleplasma were less abundant in HFD group. A high fat and low fiber diet in a native Chinese community may partially contribute to changes of intestinal microbiota composition that may potentially favor the onset and progression of gastrointestinal disorders including inflammatory, hyperplastic and neoplastic diseases.